Amazonia threatened by Brazilian President Bolsonaro’s mining agenda - Vilani, Rodrigo; Ferrante, Lucas; M. Fearnside, Philip (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
Brazilian President Jair Bolsonaro has induced a cycle of deforestation and violence in the Amazon, where dismantling environmental agencies and gutting protection policies have become a central strategy in removing barriers to predatory exploitation of natural resources. Mining is a key part of this agenda. Brazil and the international community must struggle to reverse the ongoing destruction of the Amazon.